The effect of physical factors on the production of α-Amylase from isolate 1B using response surface methodology - Kamaruddin, Nadia (2018)
Study of α-amylase is still ongoing because of its role in industry. Therefore, an enhancement should be done in α-amylase production along with the current technology. The main objective of this study is the optimization of culture conditions or physical factors to enhance α-amylase production. A-amylase producing bacteria were screened basically from various stock cultures of soil that has been isolated by previous student. The bacterial isolates for amylase production were proved by a hydrolysis test using iodine method. Statistical experimental design proposed by RSM was employed to optimize the physical conditions such as pH, temperature and agitation to enhance α-amylase production from isolate 1B. Response Surface Methodology (RSM) with Central Composite Design (CCD) was applied for this purpose. Three levels were chose as independent variable in this experimental design to test the physical factors of α-amylase. Data obtained helps to provide optimum value of each physical factor respectively. Highest amylase activity obtained among the experimental design was 1.494 U/ml/min while commercial amylase was 1.447 U/ml/min under optimum conditions. The most significant among these independent variables were initial pH and temperature which maximized amylase activity.